2023
DOI: 10.3390/ph16060831
|View full text |Cite
|
Sign up to set email alerts
|

Infoveillance and Critical Analysis of the Systematically Reviewed Literature on Dimethyltryptamine and the “God Molecule”

Abstract: Aboriginals of Latin America have used DMT (N,N-dimethyltryptamine) in ritualistic ceremonies for centuries. Nevertheless, there are limited data on web users’ interest concerning DMT. We aim to review the literature and explore the spatial–temporal mapping of online search behavior concerning DMT, 5-MeO-DMT, and the Colorado River toad via Google Trends over the past 10 years (2012–2022) while using 5 search terms: “N,N-dimethyltryptamine”, “5-methoxy-N,N-dimethyltryptamine”, “5-MeO-DMT”, “Colorado River toad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Three review articles were published [ 18 , 19 , 20 ]. Al-Imam et al [ 18 ] provided information about dimethyltryptamine, an indole alkaloid found in several plant species and the Colorado River toad ( Incilius alvarius ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three review articles were published [ 18 , 19 , 20 ]. Al-Imam et al [ 18 ] provided information about dimethyltryptamine, an indole alkaloid found in several plant species and the Colorado River toad ( Incilius alvarius ).…”
mentioning
confidence: 99%
“…Three review articles were published [ 18 , 19 , 20 ]. Al-Imam et al [ 18 ] provided information about dimethyltryptamine, an indole alkaloid found in several plant species and the Colorado River toad ( Incilius alvarius ). The authors described the historical uses, as well as pharmacological and toxicological uses of this alkaloid and discussed its legal aspects.…”
mentioning
confidence: 99%